Assessing food security in Yemen: An innovative integrated, cross-sector, and multilevel approach - Ecker, Olivier; Breisinger, Clemens; McCool, Christen; Diao, Xinshen; Funes, José; You, Liangzhi; Yu, Bingxin (International Food Policy Research Institute, 2010)
The lack of updated information about food security is of concern to many countries, especially during and after economic crises, natural disasters, and conflicts. In this paper we present an analytical framework for assessing the effects of such crises on food security. This methodology can compensate for the lack of recent data in the aftermath of various crisis situations and thus provide important information to policymakers. We apply this methodology to Yemen, a country where the recent food price crisis and global economic recession have been especially damaging. Little is known about how the recent triple crisis (food, fuel, and financial crisis) has affected food security and what the current state of food security is on the macro- (national) and microlevels (local). The results of our findings suggest an alarming state of food insecurity. Food security at the macrolevel has dramatically deteriorated in recent years, and it is projected that the country will remain highly vulnerable to external shocks in the future if no action is taken. At the household level we found that 32.1 percent of the population in Yemen is food insecure and that 57.9 percent of all children are malnourished. Rural-urban inequalities are high in Yemen. The number of food-insecure people living in rural areas (37.3 percent) is more than five times higher than in urban areas (17.7 percent). Underweight children and children with stunted growth are found more commonly in rural than urban areas. Major challenges for food security are the lack of job-creating growth within the oil-dependent economic structure; a distorted economic incentive system, coupled with an inefficient social transfer system rapidly depleting oil and water resources; and the growing production and consumption of qat.